2019
DOI: 10.3390/toxins11010054
|View full text |Cite|
|
Sign up to set email alerts
|

Regional Sub-Saharan Africa Total Diet Study in Benin, Cameroon, Mali and Nigeria Reveals the Presence of 164 Mycotoxins and Other Secondary Metabolites in Foods

Abstract: In the framework of the first multi-centre Sub-Saharan Africa Total Diet Study (SSA-TDS), 2328 commonly consumed foods were purchased, prepared as consumed and pooled into 194 composite samples of cereals, tubers, legumes, vegetables, nuts and seeds, dairy, oils, beverages and miscellaneous. Those core foods were tested for mycotoxins and other fungal, bacterial and plant secondary metabolites by liquid chromatography, coupled with tandem mass spectrometry. The highest aflatoxin concentrations were quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 56 publications
4
38
0
Order By: Relevance
“…The water stress caused by drought weakens the plant defence and increases its susceptibility to mould infection and aflatoxin production [96], which may be further enhanced if the crop is harvest in the rainy season. A recent survey on the contamination of food products of West Africa Sub-Saharan countries revealed that aflatoxin contamination of crop samples collected during the rainy season was significantly higher than those collected during the dry season [75]. Similar observation could be made from a comprehensive survey on aflatoxin contamination of various foods in Thailand for the period of 1969-1970 [107-108] (see also Table 6).…”
Section: Crop Contaminationsupporting
confidence: 59%
See 1 more Smart Citation
“…The water stress caused by drought weakens the plant defence and increases its susceptibility to mould infection and aflatoxin production [96], which may be further enhanced if the crop is harvest in the rainy season. A recent survey on the contamination of food products of West Africa Sub-Saharan countries revealed that aflatoxin contamination of crop samples collected during the rainy season was significantly higher than those collected during the dry season [75]. Similar observation could be made from a comprehensive survey on aflatoxin contamination of various foods in Thailand for the period of 1969-1970 [107-108] (see also Table 6).…”
Section: Crop Contaminationsupporting
confidence: 59%
“…Farming activities are essentially managed for subsistence by smallholders facing technical and socio-economic challenges that hamper any efforts to restrain aflatoxin contamination [71][72][73]. Moreover, the staple crops grown, such as peanut, maize, sorghum, rice, sunflower, and cottonseed are good substrates for aflatoxin production [74][75].…”
Section: Crop Contaminationmentioning
confidence: 99%
“…According to the World Health Organisation (WHO), AFLs destroy 25% of the world's crops annually [4]. Not only are AFLs carcinogenic, but these mycotoxins have also been associated with growth impairment in children [5]. Currently, AFL contamination is a large problem for undeveloped areas of Africa and Asia, but it might soon include Europe and both the North and South America continents.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high toxicity of mycotoxins, occurrence studies and exposure assessment in different regions of the world (especially those without a food safety regulation system) are relevant aspects, LC-MS/MS being the technique of choice for multi-mycotoxin analysis. In the framework of the first multi-center Sub-Saharan Africa Total Diet Study (SSA-TDS), 194 composite samples of cereals, tubers, legumes, vegetables, nuts and seeds, dairy, oils, beverages and miscellaneous were tested for mycotoxins [11]. The results show that populations from North Cameroon and Benin may suffer chronic and simultaneous exposure to AFB1, FB1, STC, OTA, and CIT, which are prevalent in their diet.…”
mentioning
confidence: 99%